Association between Elevated Plasma Homocysteine and Low Skeletal Muscle Mass in Asymptomatic Adults - Choi, Jae-Hyeong; Seo, Jin-Woo; Lee, Mi-Yeon; Lee, Yong-Taek; Yoon, Kyung Jae; Park, Chul-Hyun (Endocrinology and metabolism (Seoul), 2022)
Background: Homocysteine has been drawing attention with a closed linkage with skeletal muscle. However, the association of hyperhomocysteinemia with decreased skeletal muscle mass remains unclear. We aimed to investigate the association of hyperhomocysteinemia with low skeletal muscle mass (LMM) in asymptomatic adults.Methods: This was a cross-sectional study of 114,583 community-dwelling adults without cancer, stroke, or cardiovascular diseases who underwent measurements of plasma homocysteine and body composition analysis from 2012 to 2018. Hyperhomocysteinemia was defined as >15 μmol/L. Skeletal muscle mass index (SMI) was calculated based on appendicular muscle mass (kg)/height (m)2. Participants were classified into three groups based on SMI: “normal,” “mildly low,” and “severely low.”Results: The prevalence of hyperhomocysteinemia was the highest in subjects with severely LMM (12.9%), followed by those with mildly LMM (9.8%), and those with normal muscle mass (8.5%) (P for trend <0.001). In a multivariable logistic regression model, hyperhomocysteinemia was significantly associated with having a mildly LMM (odds ratio [OR], 1.305; 95% confidence interval [CI], 1.224 to 1.392) and severely LMM (OR, 1.958; 95% CI, 1.667 to 2.286), respectively. One unit increment of log-transformed homocysteine was associated with 1.360 and 2.169 times higher risk of having mildly LMM and severely LMM, respectively.Conclusion: We demonstrated that elevated homocysteine has an independent association with LMM in asymptomatic adults, supporting that hyperhomocysteinemia itself can be a risk for decline in skeletal musculature.